Case Report: Pembrolizumab in a patient with preexisting paraneoplastic dermatomyositis and sarcomatoid urothelial carcinoma. Searching for balance - Torniai, Mariangela; Martino, Giuseppe Pio; Gucciardino, Calogero; Angelici, Stefano; Bisonni, Renato (Frontiers in Immunology, 2025)
Dermatomyositis (DM) is an uncommon systemic autoimmune disorder classified as one of the idiopathic inflammatory myopathies (IIM). DM could also represent a manifestation of an underlying neoplasm with a relative risk of cancer globally ranging from 3% to 8%. Owing to the strong connection between immunosurveillance and cancer progression, the management of paraneoplastic DM represents a challenging issue. To complicate matters is the advent of cancer immunotherapy, that might interfere with self-tolerance with a true risk of previous autoimmune disorders re-exacerbation. We report the case of a 50-year-old patient with advanced urothelial bladder cancer and preexisting paraneoplastic DM treated with pembrolizumab. On the basis of our experience, previous paraneoplastic DM might not necessarily represent an absolute contraindication for ICIs treatment. Furthermore, this case might suggest a role of intravenous immunoglobulins (IVIG) in preventing DM reactivation, underling the importance of a multidisciplinary approach.